(untitled) (Actual Problems of Psychology in Educational Institutions, 2019)
The article reveals the essence and features of interactive teaching methods, describes the characteristics of their varieties and the theoretical substantiation of these methods as effective means of enhancing students’ cognitive activity in the educational process of the university